Grindability Of Fine Particle Gold Ore Using Vertical Stirred Mill - Abd Karim, Amirul Aiman (Universiti Sains Malaysia, 2018)
The ore mineral in earth are decreasing due to the exploration of the human being activity for the mineral and development purpose. Including mining activity which they mine the ore underneath or on the surface of the Earth. This cause the grade of the precious ore decreasing, including gold. In Malaysia, they consider low grade ore compared to the previous year. With low-grade ore they face numbers of challenge to fully extract the gold ore for the goods. This research highlight about the processing of gold ore to free the gold particle so the leaching process can extract the golf much more efficient. This study used vertical stirred mill to understand the effective parameter to reduce the size of fine ore particle so that the gold can be liberated and determine the smallest size it can produces.